THE RELATIONSHIP BETWEEN ACADEMIC BURNOUT AND QUARTER LIFE CRISIS AMONG FINAL-YEAR NURSING STUDENTS: A CROSS-SECTIONAL STUDY - Endang Mei Yunalia; Idola Perdana Sulistyoning Suharto (Bagian Keperawatan Fakultas Kedokteran Universitas Sriwijaya, 2026)
Aim: The final stage of nursing education represents one of the most psychologically challenging periods for students, as they must navigate demanding academic responsibilities while confronting the uncertainties of transitioning into professional life as future nurses. These compounding pressures create a conducive environment for the emergence of both academic burnout and quarter life crisis among nursing students. This study aimed to examine the relationship between academic burnout and quarter life crisis among final-year nursing students. Method: This study employed a quantitative approach with a correlational analytic design and cross-sectional method. The population consisted of final-year nursing students. A total of 84 final-year nursing students were recruited using a total sampling technique. The instruments used were the Maslach Burnout Inventory-Student Survey (MBI-SS) adapted into Indonesian to measure academic burnout, and the Quarter Life Crisis questionnaire. Data analysis was performed using the Spearman Rank correlation test with a significance level of α = 0.05. Result: Nearly half of the respondents experienced moderate academic burnout (48.8%), while more than half of the respondents experienced quarter life crisis at a high level (52.4%). The Spearman Rank correlation analysis demonstrated a significant positive association between academic burnout and quarter-life crisis (p = 0.000; r = 0.504), indicating that higher levels of academic burnout were associated with higher levels of quarter-life crisis, with a moderate correlation strength. Conclusion: A significant positive correlation was found between academic burnout and quarter life crisis among final-year nursing students, indicating that the higher the academic burnout experienced by students, the higher the quarter life crisis they feel.